Liver function trends after biliary decompression in obstructive jaundice: a clinico-pathological-biochemical study - Lal, Mohan; Dayal, Prabhu (International Surgery Journal, 2019)
Background: Liver functions tests suggest the underlying cause, estimate the severity, assess prognosis and monitor efficacy of therapy. Severity of liver dysfunction when performed serially may predict prognosis and may be helpful in assessing response to medical therapy or a surgical intervention. Methods: The data was collected in thirty cases of surgical obstructive jaundice in terms of age, sex, etiology, clinical presentation, surgical intervention for biliary drainage and the laboratory liver biochemical and coagulation profiles on a day prior to surgical intervention and post-operatively on 1st week and 4th week were recorded. Results: Of total 30 patients 56.66% were females. Patients with 73.68% of benign disease and 100% of malignant disease were of age more than 40 years. 63.33% of patients had benign cause for biliary obstruction. Choledochoithiasis and periampullary carcinoma were two most common causes of obstructive jaundice. The commonest complaints were; yellowish discolouration of sclera and skin, high colored urine (100%) and acholic stool (70%). Hepatomegaly, palpable gallbladder and ascites were observed in only malignant conditions. Serum bilirubin and transaminases were significantly higher in patients with malignant lesions on pre-operative and postoperative assessment. After decompression the rate of fall of serum bilirubin, serum glutamic-oxaloacetic transaminase and SGPT were almost identical in both benign and malignant biliary obstructions. However, a better biochemical recovery profile was observed in patients with benign lesions, as they returned to normal by 4 weeks but remained at 2 to 3 times of the normal in malignant lesions. Conclusions: Sequential biochemical assessment of liver functions has diagnostic as well as prognostic value in surgical obstructive jaundice.